Evaluating the Impact of REDD+ Interventions on Household Forest Revenue in Peru - Solis, D.; Cronkleton, P.; Sills, E.O.; Rodríguez Ward, D.; Duchelle, Amy E. (Frontiers Media, 2021)
REDD+ was conceived as a system of incentives for reducing emissions from deforestation and degradation. While this could include many different types of interventions to reduce deforestation and degradation, a consensus has emerged that they should safeguard and “do no harm” to the forest-based livelihoods of local people. Many REDD+ projects have been designed to incentivize forest conservation and support local livelihoods by promoting sustainable use of the forest, hence increasing the revenues earned by local households from forest products. We examine two such projects in the Peruvian Amazon, using panel survey data from over 400 households gathered in 2011 and 2014. In the 3 years between surveys, we observed a severe decline in forest revenue. However, by using a BACI study design and matching, we show that this decrease was not caused by the REDD+ interventions. Thus, REDD+ “did no harm” to local people, at least in terms of forest revenues in the early phases of these two projects in the Peruvian Amazon.